Intestinal Infestations in Under-Five Children in Zambia - Kamukwamba Mwale; Seter Siziya, PhD, FRSS (Global Health and Education Projects, Inc., 2016)
Background: Intestinal infestations are of considerable public health importance in Zambia and elsewhere in Africa. Children aged less than 5 years are at the highest risk of infection. Interventions for prevention and control of these infestations require identification of their determinants. This study investigates the determinants of intestinal infestations in children below 5 years of age admitted to a children's hospital and assesses the most prevalent of the helminthes. Methods: This was a hospital based cross-sectional study conducted at Arthur Davison Children's Hospital, Ndola, Zambia. Socio-demographic data of study participants and possible determinants for occurrence of intestinal infestations were collected using structured questionnaires. Stool samples were collected and examined for presence of parasites using direct techniques. The Pearson's Chi-square and Fisher's exact tests were used to establish associations. Results: Present study had 148 participants out of the expected 165, making a respondent rate of 89.7%. Over half of the participants were male (50.6%), and 68.9% were above the age of 2 years. Prevalence of intestinal infestations was 19.6%, and the most prevalent parasite was Ascaris lumbricoides. Factors independently associated with worm infestation were father's employment (AOR = 0.41; 95 % CI [0.19, 0.90]) and history of prior worm infestation (AOR = 6.54; 95 % CI [3.28, 13.03]). Conclusion: Intestinal infestations particularly Ascaris lumbricoides were more prevalent in this study. There should be policy towards countrywide deworming programs and enhanced hygiene. Key words: Intestinal Infestations • Under Five Children • Ascaris Lumbricoides • Zambia Copyright © 2015 Mwale and Siziya. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.